2013
DOI: 10.1136/bmjspcare-2012-000396
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting recruitment to an observational multicentre palliative care study

Abstract: ObjectivesTo identify those factors which adversely affected recruitment to a large multicentre palliative care study.MethodsPatient accrual to a multicentre, observational, palliative care study was monitored at three critical junctures in the research process. (1) Eligibility—did the patient fulfil the study entry criteria? (2) Accessibility—was it possible to access the patient to be able to inform them about the study? (3) Consent—did the patient agree to participate in the study? The reasons why patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
0
41
1
Order By: Relevance
“…Ideally, identical procedures should have been followed everywhere, although a complete standardisation is difficult as collaborators may have restricted access to patients. However, with more than 1600 patients, we believe that the sampling strategy did not introduce a substantial bias, compared to other studies in PC or advanced cancer, although it cannot be ruled out that the frailest patients were not included 21 35…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ideally, identical procedures should have been followed everywhere, although a complete standardisation is difficult as collaborators may have restricted access to patients. However, with more than 1600 patients, we believe that the sampling strategy did not introduce a substantial bias, compared to other studies in PC or advanced cancer, although it cannot be ruled out that the frailest patients were not included 21 35…”
Section: Discussionmentioning
confidence: 95%
“…Thus, efforts must be taken to optimise the generalisability of research findings. Routine data collections may be useful,34 and the registration of non-participants in studies provides a more complete picture of PC patients 21 35. Another recommendation is related to the need for a standardised, uniform description of patient characteristics, a shortcoming that has been addressed for decades 36 37.…”
Section: Discussionmentioning
confidence: 99%
“…The PiPS which recruited palliative patients from 18 palliative services in the UK had a 43% recruitment in the hospice setting, demonstrating that access to palliative patients was significantly easier in the hospice as compared to other settings. 6 The PiPS study and the Rees and Hardy study, which developed a process of advance consent to enable research to be undertaken in patients in the terminal phase, reported that very few patients were distressed when approached. Rees and Hardy also reported that the consent process can be very time consuming and emotionally draining for staff.…”
Section: Discussionmentioning
confidence: 99%
“…Obstacles to research include the following: the heterogeneous nature of the patient population due to variants in primary disease and concomitant and independent comorbidities, the high prevalence of cognitive problems which affect capacity, the unstable nature of the disease process, the lack of research infrastructure and experience in palliative care teams and 'gatekeeping' (ie, preventing access to potential research participants by clinical staff ). 6 However, research is essential to improve patient care and for palliative care to develop as an evidence-based specialty. 7 In this paper, we evaluated the feasibility of collecting multiple biological samples (urine) from hospice patients in the last weeks and days of life, including patients who lost the capacity to give consent.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The study by Stone et al 2 published in this issue of BMJ Supportive & Palliative Care highlights this. Stone et al demonstrated that in a carefully planned, non-interventional study with rather simple assessments, less than one-tenth of the patients admitted to the relevant units were included.…”
mentioning
confidence: 96%